Management of Agricultural Waste - Parab, Soniya; Patel, Chitra (Journal of Advanced Research in Service Management, 2022)
Agricultural wastes are non-product outputs of production and process of agricultural goods which will contain material that may profit man however whose economic values are less than the cost of collection, transportation and processing for beneficial use. Estimates of agricultural waste arising are rare, however they’re typically thought of as contributory a big proportion of the whole waste material within the developed world. Agricultural development is typically in the midst of wastes from the irrational application of intensive farming ways and therefore the abuse of chemicals utilized in cultivation, remarkably touching rural environments particularly and the global environment in general. Generally, agricultural wastes are generated from variety of sources notably from cultivation, placental and cultivation. These wastes are presently used for variety of applications through the ‘3R’ strategy of waste management. Agricultural waste incorporates a toxicity potential to plant, animals and human through many direct and indirect channels. The effects of these toxic agricultural wastes on the environment were discussed as well as their cure.